Factors influencing employee loyalty / Nur Shahirah Khairul Annuar - Khairul Annuar, Nur Shahirah (Faculty of Business Management, 2017)
The business world as we know it is changing by the minute, as globalization takes place. Cross border transactions has increased tremendously due to globalization where goods and services are shipped throughout the world. However, services are not tangible, it comes along with the person who has the knowledge and skills to perform it. Thus, besides competing for market and customers, organizations must now compete with each other for the best human talent. This is because organizations are more aware of the importance of these talents. They are the linchpins of the organization and are needed to implement the strategies to achieve organizational success. However, maintaining human talent is not an easy task as there will always be other organizations that can offer better pay and/or benefits. PETRONAS Chemicals Berhad (PCG) is no exception to this problem. In order to retain and avoid having the best human talent stolen from their firm, it is imperative that they understand what are the factors that have the influence on employee loyalty. Thus, this research aims to study the factors influencing employee loyalty, specifically in PCG, located in PETRONAS Twin Towers. The determinants of employee loyalty based on literature review are commitment, motivation, belongingness and career development. Four hypotheses were made afterwards. 175 questionnaires were distributed physically to PCG’s employees by using non-probability convenience sampling technique at PETRONAS Twin Towers. However, only 165 of them were useable. The data collected were analyzed using the SPSS software. The findings from analysis show that only commitment, belongingness and career development have a significant impact on employee loyalty. Based on the findings, recommendations were then made.